A phenomenological description of biomass powder combustion in internal combustion engines. (1st July 2023) - Stover, Luke; Caillol, Christian; Piriou, Bruno; Mayer-Laigle, Claire; Rouau, Xavier; Vaïtilingom, Gilles
Abstract: An alternative strategy to implement the use of biofuels in internal combustion engines is to use minimally refined biofuels and redirect savings to engine modifications. While the idea of using coal dust in engines has been studied extensively, the combustion of micronized biomass powder has not been given due consideration. To understand and describe the phenomena, several exploratory tests were conducted in a single-cylinder diesel engine. The engine was operated with micronized powders of cellulose, wood char, wheat straw, chestnut wood, rice husk and pine bark with an average particle size of 20 μm. Cellulose combustion was found to be difficult to initiate, mostly because of endothermic depolymerization reactions. Despite its lower volatile content, wood char showed improved performance over cellulose. Both combustible powders presented premixed-like heat release profiles. Carbon monoxide, released during partial combustion of submicronic particles in the early stages of the compression stroke was found to be the main combustion driver. Nitrogen testing with wheat straw highlighted the occurrence of a torrefaction process leading to the formation of water with small amounts of pyrolysis products. A numerical study using adimensional numbers indicates that the transition from kinetically-limited to convection-limited CO production process is restricted to particles smaller than 50 μm as in-cylinder temperatures increase. Highlights: A phenomenological description of biomass powder combustion within ICE is proposed. Influence of cellulose, volatiles and size of particles on combustion is studied. Partial oxidation producing CO which in turn burns in homogeneous phase is shown. Larger-sized particle fraction undergoes a kinetically-limited conversion process.